Graphic methods for ecosensitivity assessment of the somatotypes components - Toteva, M. V.; Nacheva, A. G. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The presented method visualizes the specific interdependent changes in the somatotype components during the postnatal ontogenesis, the period of training and is the basis for creation of the graphic somatotype models of elite athletes. The authors believe that this new visual presentation can find its application in sports practice and as prevention and evaluation of treatment in some diseases.